Welfare Reform in the United States - Nedde, Ellen (IMF Working Papers; Working Paper ;, 1995)
This paper reviews the structure and trends of the U.S. welfare system and the U.S. Administration's reform proposals. It shows that, despite the attention the program receives, the welfare program is actually quite small and has experienced moderate rates of growth. However, the system does face serious problems. In particular, its structure sets up strong financial disincentives to paid employment and saving at the same time that its low level of benefits fails to lift low-income children and their families out of poverty.